The hive and the honey : stories - Yoon, Paul (Marysue Rucci Books, an imprint of Simon & Schuster, Inc., 2023)
Portraying the vastness and complexity of diasporic communities, this unflinching and unforgettable collection of stories from the beloved award-winning author confront themes of identity, belonging and the collision of cultures across countries and centuries.